Dendritic cells process synthetic long peptides better than whole protein, improving antigen presentation and T‐cell activation. Issue 10 (5th August 2013) - Rosalia, Rodney A.; Quakkelaar, Esther D.; Redeker, Anke; Khan, Selina; Camps, Marcel; Drijfhout, Jan W.; Silva, Ana Luisa; Jiskoot, Wim; van Hall, Thorbald; van Veelen, Peter A.; Janssen, George; Franken, Kees; et al.
<x xml:space="preserve">Abstract</x> The efficiency of antigen (Ag) processing by dendritic cells (DCs) is vital for the strength of the ensuing T‐cell responses. Previously, we and others have shown that in comparison to protein vaccines, vaccination with synthetic long peptides (SLPs) has shown more promising (pre‐)clinical results. Here, we studied the unknown mechanisms underlying the observed vaccine efficacy of SLPs. We report an in vitro processing analysis of SLPs for MHC class I and class II presentation by murine DCs and human monocyte‐derived DCs. Compared to protein, SLPs were rapidly and much more efficiently processed by DCs, resulting in an increased presentation to CD4+ and CD8+ T cells. The mechanism of access to MHC class I loading appeared to differ between the two forms of Ag. Whereas whole soluble protein Ag ended up largely in endolysosomes, SLPs were detected very rapidly outside the endolysosomes after internalization by DCs, followed by proteasome‐ and transporter associated with Ag processing‐dependent MHC class I presentation. Compared to the slower processing route taken by whole protein Ags, our results indicate that the efficient internalization of SLPs, accomplished by DCs but not by B or T cells and characterized by a different and faster intracellular routing, leads to enhanced CD8+ T‐cell activation.